Panama : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2001)
Under the Stand-By Arrangement, Panama has achieved good economic performance owing to its strong financial reform and low inflation. Executive Directors welcomed this step, and stressed the need to improve fiscal consolidation and tax reforms, tighten monetary stance, strengthen public finances, and accelerate structural reforms. They agreed that the country's economic and financial statistics are adequate for surveillance and program purposes, and encouraged the authorities to address remaining weaknesses, especially in the balance of payments and national accounts.